2021
DOI: 10.3390/ijms22094607
|View full text |Cite
|
Sign up to set email alerts
|

A Crucial Role of Mitochondrial Dynamics in Dehydration Resistance in Saccharomyces cerevisiae

Abstract: Mitochondria are dynamic organelles as they continuously undergo fission and fusion. These dynamic processes conduct not only mitochondrial network morphology but also activity regulation and quality control. Saccharomyces cerevisiae has a remarkable capacity to resist stress from dehydration/rehydration. Although mitochondria are noted for their role in desiccation tolerance, the mechanisms underlying these processes remains obscure. Here, we report that yeast cells that went through stationary growth phase h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The closest comparison we could find was a recent study of chronic kidney disease showing a slow and gradual change in mitochondrial dynamics from fusion to fission in remnant renal masses from day 2 to day 28 after 5/6 nephrectomy in rats [ 55 ]. Another example of the critical role of shifting the mitochondrial dynamic equilibrium was seen in S. cerevisiae , in that it employed a delicate balance of fusion and fission to adjust mitochondrial dynamics in a stationary growth phase to resist prolonged dehydration stress [ 56 ]. These examples, together with our observations in human cells, signify the importance of mitochondrial network dynamics in both early stress response and late adaptation to the changing microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The closest comparison we could find was a recent study of chronic kidney disease showing a slow and gradual change in mitochondrial dynamics from fusion to fission in remnant renal masses from day 2 to day 28 after 5/6 nephrectomy in rats [ 55 ]. Another example of the critical role of shifting the mitochondrial dynamic equilibrium was seen in S. cerevisiae , in that it employed a delicate balance of fusion and fission to adjust mitochondrial dynamics in a stationary growth phase to resist prolonged dehydration stress [ 56 ]. These examples, together with our observations in human cells, signify the importance of mitochondrial network dynamics in both early stress response and late adaptation to the changing microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Hsp70 gene reduces the viability of desiccated cysts of Artemia [16]. A genome wide screening in budding yeast revealed that respiration is a prerequisite in acquiring desiccation tolerance [17], and it is likely associated with the dynamic changes of mitochondria [18]. In yeast, due to starvation stress or lack of nutrient, stationary cells become more resistant to different stresses, via dramatic decrease in overall growth, enriched lipids, trehalose and proteins, and thickened cell wall that are necessary to encounter heat, cold, or desiccation stress [8,19].…”
Section: Introductionmentioning
confidence: 99%
“…The role of mitochondria in desiccation tolerance has already been described, but Chen et al reported on the very important role of mitochondrial dynamics in this process [ 8 ]. They demonstrated that preserved mitochondrial dynamics during the stationary phase of growth is necessary for adequate cell response to dehydration/rehydration stress.…”
mentioning
confidence: 99%